Periprocedural and long‐term outcomes of endovascular abdominal aortic aneurysm repair in cardiology practice. Issue 7 (11th June 2014) - Basoor, Abhijeet; Patel, Kiritkumar C.; Halabi, Abdul R.; Todorov, Mina; Senthilvadivel, Prashanth; Choksi, Nishit; Phan, Thanh; LaLonde, Thomas; Yamasaki, Hiroshi; DeGregorio, Michele
<x xml:space="preserve">Abstract</x> Background Endovascular repair of abdominal aortic aneurysm (AAA) has recently been made a class I indication in the treatment of AAA. In comparison to the conventional open surgical treatment, endovascular AAA repair (EVAR) is associated with equivalent long‐term morbidity and mortality rates. Vascular surgeons perform majority of EVAR. There are no reports for the long‐term results of this intervention performed by interventional cardiologists. We present one of the first reports of periprocedural and long‐term outcomes of EVAR performed by interventional cardiologists. Methods Retrospective chart review on patients with attempted EVAR between September 2005 and January 2011 was performed. Included cases were all consecutive patients who had attempted EVAR by interventional cardiologists. Results During the study period EVAR was attempted in 170 patients, with 27% being women. The mean age was 74 years (range 52–93). The endovascular graft placement was successful in 96% (163/170) of patients. Procedure failures were more common in women (6 of 46 vs 1 of 124, P = 0.003). The 30‐day mortality was 1.8 % (3 of 170). In patients with successful EVAR the mean follow‐up was 30 months and mean length of hospital stay was 3.5 ± 3.2 days. Major periprocedural complications were noted in 9% patients (15 of 167). During follow‐up, six patients (3.5%) required re‐intervention and additional 16 patients died with no aneurysm related deaths. Conclusion EVAR primarily performed by interventional cardiologists demonstrates high periprocedural and long‐term success rates. A higher EVAR failure rate has been observed in women. © 2014 Wiley Periodicals, Inc.